2020
DOI: 10.5173/ceju.2020.0252
|View full text |Cite
|
Sign up to set email alerts
|

How has the COVID-19 pandemic impacted Polish urologists? Results from a national survey

Abstract: Introduction Poland was initially less affected by the coronavirus disease 2019 (COVID-19) pandemic, however, severe restrictions, and health care restructuration have impacted all areas of medicine, including urology. Therefore, we aimed, via an online survey, to examine the impact of the COVID-19 pandemic on Polish urologists and urology residents. Material and methods Between May 15 and June 6, 2020, 229 (28.63% response rate) urologists and urology residents respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…In our study, more than one-third of elective surgeries were postponed in Egypt and the UAE, compared to half in the KSA. This finding is consistent with the recommendations of international organizations and the measures adopted to mitigate the negative impacts of the COVID-19 epidemic [ 19 21 ]. Most Saudi governmental hospitals applied these measures [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, more than one-third of elective surgeries were postponed in Egypt and the UAE, compared to half in the KSA. This finding is consistent with the recommendations of international organizations and the measures adopted to mitigate the negative impacts of the COVID-19 epidemic [ 19 21 ]. Most Saudi governmental hospitals applied these measures [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…In a survey of Polish attending and resident urologists, almost 80% of respondents noticed that the pandemic had negative psychological effects on their colleagues, with 57.6% reported feeling increased sadness, anxiety, or increased stress levels and > 75% indicating a negative impact on family relations [ 29 ]. Respondents were mostly distressed due to the uncertainty regarding the duration of the pandemic (68.56%), implemented restrictions (51.97%), and the possibility of exposing relatives to COVID-19 (51.53%) [ 29 ]. Almost all (96.5%) respondents believe the pandemic had a moderate to high impact on their everyday clinical practice, and a majority of residents (62%) felt that the pandemic would harm their training [ 29 ].…”
Section: Physical and Mental Well-beingmentioning
confidence: 99%
“…Respondents were mostly distressed due to the uncertainty regarding the duration of the pandemic (68.56%), implemented restrictions (51.97%), and the possibility of exposing relatives to COVID-19 (51.53%) [ 29 ]. Almost all (96.5%) respondents believe the pandemic had a moderate to high impact on their everyday clinical practice, and a majority of residents (62%) felt that the pandemic would harm their training [ 29 ]. A systematic review from August 2020 analyzing mental health issues among healthcare workers during the COVID-19 pandemic revealed a pooled prevalence rate of anxiety of 22.8% across 12 different studies [ 30 ].…”
Section: Physical and Mental Well-beingmentioning
confidence: 99%
“…In many countries in Europe and around the world, COVID-19-related surveys have already been conducted among residents of ophthalmology [7,8] and other specialties, such as surgery [9], urology, [10] and anaesthesiology. Although the above-mentioned medical staff are not directly involved in the fight against the pandemic, the surveys revealed that the pandemic had a significant impact on the course of residency and the functioning of their departments [11,12]. We decided to use a survey for this study, the aim of which was to collect the opinions of ophthalmology residents on the impact of the COVID-19 pandemic on their working conditions, mental health, and specialisation training.…”
Section: Introductionmentioning
confidence: 99%